Efficient Cross-Coupling Reactions of (Pivaloyloxymethyl)zinc Chloride - Blanc, Romain; Groll, Klaus; Bernhardt, Sebastian; Stockmann, Paul N.; Knochel, Paul (Synthesis, 2014)
(Pivaloyloxymethyl)zinc chloride, obtained by an iodine–magnesium exchange and subsequent transmetalation, shows a much higher reactivity in Negishi cross-couplings than the corresponding zinc organometallic, prepared by direct zinc insertion. Furthermore, a substituted derivative of (pivaloyloxymethyl)zinc chloride is prepared starting from pivaloyloxymethyl sulfoxide using TMPZnCl·LiCl (TMP = 2,2,6,6-tetramethylpiperidyl), followed by a sulfoxide–magnesium exchange.
Keywords: organozinc reagents; carbenoids; cross-coupling; palladium; sulfoxides